Filipino Libang: University Student’s Leisure Ecology - Uy, Danielle Naomi (Future Science / FSH-PH Publications, 2025)
This mixed-methods study defined the leisure ecology of Filipino university students through exploration of their leisure motivation, leisure satisfaction, and happiness through their leisure pursuits. Data were collected using surveys, while quantitative analysis utilized Factor Analysis to define motivation and satisfaction factors alongside a standardized happiness measure. Factor analysis revealed that the students’ leisure ecology is primarily oriented toward competence, relaxation, and the cultural pursuit of ligaya (deep, lasting happiness). Despite high leisure motivation and leisure satisfaction being significantly correlated (r>0.60), their correlation with the standardized happiness measure was low (r=0.20), suggesting ligaya is gained through distinct, culturally embedded pathways, while significant gender differences emerged in specific motivational and satisfaction factors (p<0.05). This study also identified specific cultural components such as libang (soulful easing through carefree amusement), kapwa (shared inner self), and barkada (chosen peer circle) as profound mechanics of this unique leisure ecology. These findings underscore the local culture’s influence on leisure, giving insights for cultivating well-being among Filipino university students.